Factors Influencing The Increase in Violence Against Women: A Systematic Review - Dini Rahmayani; Muhammad Modi Lakulu; Husin; Ahmad Syahlani; Umi Hanik Fetriyah; Agus Byna (Universitas STRADA Indonesia, 2025)
Background: Violence against women is a global public health problem, with an estimated one in three women experiencing physical, emotional, or sexual violence. Approximately one in three women worldwide have experienced physical or sexual violence. Intimate partners have the right to beat their female partners, violence experienced by women is often underreported. Purpose: to describe the causal factors that contribute to violence against women. Methods: Systematic review method, data sources, study selection, search, eligibility criteria, data collection, and literature taxonomy. These articles were published over a 6-year period from 2018 to 2023 with selection using PRISMA. the results found 12 articles that had been studied extensively to map the research area. Results: 61 variables consisting of two parts, namely demographic characteristics and factors that contribute to the cause were studied in the article. Based on the results of the article analysis, it was found that the dominant factors studied, and had a significant relationship to the occurrence of violence against women included: 1) age; 2) women's education; 3) place of residence; 4) family income; and 5) women's work. Conclusion: Based on the findings, the dominant factors are very important to be followed up in further research with an artificial intelligence (AI) approach using machine learning, which is an interdisciplinary collaboration, especially in the field of women's reproductive health, in line with the emphasis of the digital era on the use of AI.